Le Musee de Sciences Naturelles, un partenaire de l'école pour une education relative a l'environnement :du message scientifique au débat de société - Cécile Fortin-Debart (VertigO)
In France, the ministry responsible for school education propose to the teachers to developp partnership in environmental education, for example with scientific museum. The article present a classification of educative approach in the natural history museum. In a first part, we present the most of scientific approach met in the exhibitions, which are linked with the evolution of natural history. In a second part, we think that a socially critical approach is nedeed in the exhibition: the museum, which become more and more a link between scientific sphere and social sphere, offer interresting possibilities. For example, with the exhibition Nature Vive, we can show how an exhibition is able to present the museum collection with a scientific dimension associated with a socially critical approach.